KONSEP MAHABBAH JALALUDDIN RUMI - assya octafany (UIN Sunan Kalijaga Yogyakarta, 2020)
This article explores Rumi's mahabbah concept. Currently, in society, the concept of love is degrading in meaning, resulting in its constriction. This is because the concept of mahabbah, which we usually refer to as